2022
DOI: 10.1186/s12957-022-02517-1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of prehabilitation during neoadjuvant chemotherapy and interval cytoreductive surgery on ovarian cancer patients: a pilot study

Abstract: Background Cytoreductive surgery followed by systemic chemotherapy is the standard of treatment in advanced ovarian cancer where feasible. Neoadjuvant chemotherapy (NACT) followed by surgery is applicable where upfront cytoreductive surgery is not feasible because of few certain reasons. Nevertheless, surgical interventions and the chemotherapy itself may be associated with postoperative complications usually entailing slow postoperative recovery. Prehabilitation programs consist of the patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 37 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…The addition of perioperative nutritional interventions 1–2 weeks before gynecological cancer surgery showed a reduction in length of hospital-stay and post-operative complications 36. Moreover, the addition of multimodal prehabilitation programs with nutritional support during neoadjuvant chemotherapy in ovarian cancer patients undergoing interval cytoreductive improved perioperative nutritional parameters 37…”
Section: Discussionmentioning
confidence: 99%
“…The addition of perioperative nutritional interventions 1–2 weeks before gynecological cancer surgery showed a reduction in length of hospital-stay and post-operative complications 36. Moreover, the addition of multimodal prehabilitation programs with nutritional support during neoadjuvant chemotherapy in ovarian cancer patients undergoing interval cytoreductive improved perioperative nutritional parameters 37…”
Section: Discussionmentioning
confidence: 99%
“…Previously, we analyzed the role of nutritional prehabilitation in women with ovarian cancer [ 18 ]. We selected patients undergoing a prehabilitation program during neoadjuvant chemotherapy and interval cytoreductive surgery.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, there has been one further study by Miralpeix et al evaluating a prehabilitation programme after our search was performed. This pilot study also demonstrated the feasibility and safety of a multimodal prehabilitation programme before interval cytoreductive surgery in ovarian cancer patients, with significant improvement of nutritional parameters [ 33 ].…”
Section: Discussionmentioning
confidence: 99%